Kinetic study and simulation of glucose degradation through anaerobic fermentation for bioethanol production - Hussain, Sharifah Nurain; Nagalinggam, Viveganan; Shamjuddin, Amnani; Engliman, Nurul Sakinah (Karya Ilham Publishing, 2025)
As a renewable biofuel, bioethanol offers a sustainable alternative to fossil fuels, addressing the global demand for cleaner energy. The utilisation of sugar derived from biomass is one of the key strategies in advancing bioethanol production, which involves a catalytic reaction with yeast during the fermentation process. Although bioethanol fermentation has been widely studied, limited experimental validation of temperature-dependent kinetics constrains model reliability and process scalability. This work integrates experimental and modeling approaches to examine glucose degradation kinetics by Saccharomyces cerevisiae under anaerobic conditions at 30°C, 35°C, and 40°C. Results indicate that anaerobic fermentation at 30°C achieved the highest ethanol concentration of 3.11 g/L after 96 hours, with 88.5% glucose utilization. A kinetic model incorporating Monod and Hinshelwood equations was simulated using COMSOL Multiphysics software, with the Arrhenius relationship applied to describe temperature-dependent reaction rates. This study also revealed the activation energy of 9.12 kJ/mol derived from Arrhenius linear regression, which confirms the efficient kinetics at moderate temperatures. COMSOL Multiphysics® simulation validated experimental trends (R2>0.95), highlighting the model’s capability for process optimization. These findings highlight the critical role of glucose degradation kinetics in guiding the development of energy-efficient and thermally optimized fermentation processes for industrial applications.